Biological Control in Barbados - van Lenteren, Joop C.; Colmenarez, Yelitza C. [UNESP]; VanLenteren, J. C.; Bueno, VHP; Luna, M. G.; Colmenarez, Y. C. (Cabi Publishing-c A B Int, 2020)
Early classical biocontrol successes in Barbados, some in combination with natural control, were the control of: sugarcane borers, sugarcane mealybugs and West Indian cane fly in sugarcane; cottony cushion scale and citrus blackfly in citrus; coconut whitefly in palm; fall armyworm in vegetables and field crops; diamondback moth in cruciferous crops; and green scale and whitefly on fruit and ornamental trees. Recent successes concern classical biocontrol, often in combination with natural control, of: the pink hibiscus mealybug in various crops and ornamentals; sago palm scale on cycads and ornamental palm; and the citrus leaf miner and the Asian citrus psyllid in citrus. Natural control included that of: papaya mealybug in papaya; chilli thrips in various crops; and red palm mite in coconut palm, ornamentals and bananas. Parasitoids were most often used, followed by predators, while microbial agents were rarely used. Barbados has regularly served as provider of natural enemies for other islands in the Caribbean. The island has faced at least 25 arthropod invasions of pests since 2000, stressing the need for biocontrol solutions.